Case Report: A modified approach to converting ventriculoperitoneal shunt to ventriculoatrial shunt due to recurrent encapsulation of the peritoneal catheter - Zhang, YunSen; Ge, YuanHong; Liu, Yong; Zhang, Yue; Xu, RongHua; Xu, Xuejun (Frontiers in Surgery, 2025)
BackgroundHydrocephalus is a condition characterized by the accumulation of cerebrospinal fluid (CSF) in the ventricular system due to various causes, including excessive CSF production, impaired circulation, or absorption dysfunction. This condition is often accompanied by ventricular enlargement, compression of brain parenchyma, and increased intracranial pressure. Ventriculoperitoneal (VP) shunting is the first-line treatment for hydrocephalus; however, when the peritoneal catheter becomes obstructed due to encapsulation, the procedure may need to be converted to a ventriculoatrial (VA) shunt, which serves as a second-line treatment. Here, we present a case that demonstrates a rapid, simple, and minimally invasive technique for converting a VP shunt to a VA shunt. This approach eliminates the need to expose the retroauricular valve or disconnect the valve from the catheter, significantly reducing operative time and minimizing trauma.Case presentationA 61-year-old male patient presented with typical clinical features of hydrocephalus, including urinary dysfunction, gait instability, and gradually worsening cognitive decline over the course of a year, as well as corresponding imaging findings. The patient subsequently underwent a VP shunt procedure. However, within six months postoperatively, the patient experienced four episodes of shunt dysfunction due to omental encapsulation of the peritoneal catheter, leading to catheter obstruction and worsening hydrocephalus. During the first three episodes, the shunt catheter was released from omental encapsulation through laparoscopic surgery, providing temporary relief of hydrocephalus after each procedure. Following the fourth episode of peritoneal shunt dysfunction, we employed a rapid exchange technique to relocate the peritoneal catheter to the superior vena cava while preserving the ventricular catheter and shunt valve. Postoperatively, the patient's hydrocephalus-related symptoms gradually improved. At the three-month follow-up, the patient's hydrocephalus showed significant improvement, and he had returned to independent daily living.ConclusionThe rapid exchange technique is a fast, simple, and minimally invasive method for converting a VP shunt to a VA shunt, offering significant benefits in clinical practice.